التمثلات الثقافية للجمال البشري في سينما التحريك- دراسة تحليلية لفيلم الرسوم المتحركة الجميلة والوحش - عثمان, ليليا; ساحل, عبد الحميد (جامعة الوادي - University of Eloued, 2021)
تعالج هذه الدراسة موضوع يتعلق بالتمثلات الثقافية للجمال البشري في سينما التحريك، وتهدف إلى التعرف على كيفية تناول الصورة السينمائية المتحركة لمفهوم وتصورات الجمال البشري من خلال السياق الثقافي حيث قمنا باختيار عينة قصدية تتمثل في فيلم الجميلة والوحش Beauty And The Beast الصادر سنة 1991 من خلال تطبيق مقاربة التحليل السيميولوجي للباحث والناقد الفرنسي رولان بارث القائمة على قراءة الفيلم من الناحية التعينية والتضمينية للكشف عن الرسائل الصريحة والضمنية التي يقدمها الفيلم لنتوصل في الأخير إلى أن الجمال لاينحصر فيما نراه فقط بل يشمل أيضا مانشعر به ومالانراه . This study deals with a topic related to cultural representations of human beauty in animation cinema, and aims to identify how the moving cinematic image deals with the concept and perceptions of human beauty through the cultural context, where we chose an intentional sample represented in the movie Beauty And The Beast issued in 1991 through an application The semiological analysis approach of the French researcher and critic Roland Barthes, based on reading the film in terms of specific and implicit, to reveal the explicit and implicit messages presented by the film, in order to conclude in the end that beauty is not limited to what we see, but also includes what we feel and what we do not see.
The Cultural Representations of The Human Beauty in Animated Film An Analyatical Study of The Animated Film Beauty and The Beast
مقال
Keywords: سينما التحريك، الجمال البشري، ثقافة الصورة المتحركة، مفهوم الجمال، الرسوم المتحركة.; Animation Cinema, Human Beauty, Motion Picture Culture, The Concept of Beauty, Animation.